P1344 Right ventricular mass: multimodality diagnostic approach to an incidental finding. (17th January 2020) - Ambrozic, J; Kovac, A; Zbacnik, R; Ponorac, S; Kogoj, P; Dimitrovska, L; Dolenc-Strazar, Z; Antolic, B; Sinkovec, M
Abstract: : Background Cardiac masses are rare entities and often diagnostically challenging. When incidentally found multimodality diagnostic approach is warranted for further characterization and evaluation of its contribution to the patient's symptoms. Case report 62-year-old male, smoker, with a history of non-Hodgkin lymphoma treated with radiation and chemotherapy 10 years ago, was admitted due to subacute myocardial infarction. Coronary angiogram showed subacute occlusion of partly collateralized RCA, subsequently treated with dilatation and stenting. Echocardiography revealed signs of dilated cardiomyopathy with severely reduced left ventricular ejection fraction (EF 20%), that could be due to chemotherapy-related cardiotoxicity. On admission CTA was performed to exclude aortic dissection since the patient presented with very severe chest pain radiating to the back. It showed a heterogeneous formation within the right ventricle (RV) extending along the interventricular septum from the apex towards the tricuspid annulus, appearing to involve interventricular septum as well. According to the imaging characteristics the mass was suspected to be a liposarcoma (Figure A). With contrast echocardiography hypoechogenic formation in the RV on parasternal long-axis view could be visualized (Figure B). Due to previous history of malignancy PET scan was performed that revealed hypometabolic RV mass, suggesting a benign tumor, without any sign of metastasis. We decided for percutaneous biopsy that was done under intracardiac echocardiography (ICE) guidance using the view from the RV towards RV outflow tract (Figure C). Histology revealed proliferation of mature adipocytes, either orthotopic or multiplied (Figure D). To exclude well-differentiated liposarcoma FISH (fluorescent in situ hybridization) with amplification of MDM2 gene was undertaken, confirming benign lesion, most probably cardiac lipoma. It was concluded that the mass was an incidental finding, not related to the patient's symptoms and not causing any functional disturbances; therefore surgical therapy could be avoided. Conclusion: While echocardiography remains the first-line imaging modality, multimodality diagnostic approach is mandatory for evaluation and treatment decision of a newly-discovered cardiac mass. Histology provides definitive diagnosis and ICE could be helpful for guiding percutaneous biopsy, thus avoiding invasive open-heart procedures. Figure. Cardiac CTA (A), contrast echocardiography (B), intracardiac echocardiography (C) and histologic specimen (D) of the right ventricular mass (arrows).